Effect of Tempeh Supplementation on the Profiles of Human Intestinal Immune System and Gut Microbiota (Indonesian Society for microbiology, 2017)
Tempeh is a traditional fermented soybean product from Indonesia. Although tempeh is consumed as daily menu in Indonesia, its nutrigenomic study employing human has not been reported yet. On the other hand, our study in mice showed that tempeh could enhance immune system, especially by increasing secretory immunoglobulin A production in ileum and colon. Tempeh was also found to be potential in modulating the composition of gut microbiota. Therefore, the objective of this study was to analyze the impact of tempeh supplementation on the profiles of human intestinal immune system and gut microbiota analysis. This experimental design was reviewed and approved by the ethics committee. A total of 16 participants, comprising of each 8 healthy females and males, aged between 20 and 23 were recruited to this study. The volunteers consumed 200 mL milk from day 1-8 followed by consumption of 100 grams steamed tempeh each day from day 9-24. Fecal samples, which were taken on day 9 and 25, were analyzed with half sandwich ELISA for IgA enumeration while fecal samples, which were taken on day 0, 9, and 25, were analyzed for Akkermansia muciniphila enumeration employing quantitative real time PCR. The result of this study suggesting that tempeh supplementation might act as paraprobiotic and slimming agent since tempeh enhanced production of IgA and increased the number of A. muciniphila in human intestinal tract.